Early vs. delayed oral feeding after colorectal surgeries, a clinical trial - K Vejdan, M.D, Amir; Khosravi, M.D, Maliheh; Amirian, M.D, Zahra (Researcher Bulletin of Medical Sciences, 2021)
Background: The start of oral nutrition after colorectal surgery has always been an issue of debate. There is a long-standing practice of beginning oral feeding 4-5 days after surgery. However, in recent years a number of surgeons have questioned this method and in fact, have begun ordering immediate oral nutrition for their postoperative patients. The current article presents the findings of a clinical trial study, which compared the early and delayed start of oral feeding after colorectal surgery. Materials and Methods: The present clinical trial recruited 52 patients undergoing colorectal anastomosis and divided these subjects into two groups. In the control group, oral feeding started 4-5 days after the operation. In contrast, the study group commenced oral nutrition soon after surgery. The outcomes for both groups were measured in terms of demographic data, anastomotic leakage rate, nausea and vomiting, the start of bowel movements, and complications. Results: The two patient groups did not differ in their rates of ileus and diet intolerance (p=1). As for the factors of nausea and vomiting, there were no observed statistically significant differences between the study and control groups (p=0.1). The most critical outcome of the early and late start feeding groups was anastomotic leakage, for which there was no significant difference to report. The length of hospital stay was significantly shorter in the early feeding study group (3.56 days) than in the delayed feeding control group (7.36 days) (p<0.001). Defecation among patients receiving early oral nutrition was 2.8 days on the average, but 4.91 days among the control group patients, a statistically important difference (p<0.004). Conclusion: While the early start of oral nutrition after colorectal surgery resection and anastomosis does not raise postoperative risks and mortality; it does reduce postoperative complications, the length of hospital stay, and final health care costs. As a result, early feeding after surgery can be considered as a viable alternative to delayed feeding.